Persistent clinical features in paediatric patients after SARS-CoV-2 virological recovery: a retrospective population-based cohort study from a single centre in Latvia. Issue 1 (29th December 2020) - Smane, Liene; Stars, Inese; Pucuka, Zanda; Roge, Ieva; Pavare, Jana
Abstract : The COVID-19 related state of emergency in Latvia was declared on 12 March 2020. Consequently, Children's Clinical University Hospital in Riga, Latvia, established a postacute outpatient service for individuals after recovery from COVID-19. Although information regarding the epidemiology and clinical features of COVID-19 in children has accumulated, relevant reports about persistent symptoms after recovery are lacking. We aimed to determine data on COVID-19 persistent symptoms after recovery in children in Latvia. Persistent symptoms have been reported in 9 out of 30 children.